Benchmarking bulkers delivered between 2010 and 2016, identifying the effect of the EEDI introduction - Jeroen F.J. Pruyn (Journal of Shipping and Trade (JST), 2020)
The EEDI is one measure to identify the energy efficiency of a vessel. Besides EEDI there are many other aspects relevant when considering the energy efficiency quality of a vessel, most based on design insights. In this paper, a set of ten relevant indicators are identified to establish the performance of the vessel and pinpoint the source of an energy efficiency improvement. These indicators are applied to the dry bulk vessels delivered between 2010 and 2016. Finally, for all indicators with a reasonable fit, the significance of the differences between trend lines is investigated. This results in groupings with equal performance, showing a clear split between vessels delivered between 2014 and 2016 and before. This is in line with the EEDI enforcement starting 2013. However, for the vessels below 125.000 DWT, the effect so far is traced back to be an increase in contract speed only. No other aspects changed significantly enough. Above this size, a reduction in speed and power can be observed, as predicted by many scholars.
Keywords: 650; Shipping; Newbuilding; Benchmark; Energy efficiency; EEDI